O ciúme na MPB: uma análise retórica - Nunes, Célia Regina (2007)
This work shows us the importance of reading and its possibilities. We worked with sociointeract reading and one of the possibilities of facilitator text to develop the reading process in school. We brought to discussion the use of MPB like important text and appropriated to develop reader learners. We used as theoretical referential Aristotle s passion and a brief concept of old rhetoric to analyze with the new Perelman and Tyteca´s rhetoric. We detached the use of argument and metaphor in the new rhetoric and found, by means of jealousy´s representation, this presence in MPB songs of 70 s. Finally, we analyzed two MPB songs and pointed the jealousy s presence by means of passion. We followed the rhetoric s bases to identify persuasive speech in MPB and we believe that the argument be able to persuade a lot of types of audience and for phatos be reached it´s just invest in the ethos´ constitution